Optimization strategy and solution of 4G high-speed rail network - Zongzhang LI; Zhitong SHI; Yuling WANG; Kun YUAN; Zhiguo WANG; Xinchao ZHANG (Dianxin kexue)
With the development of LTE data and VoLTE services,subscribers pay more and more attention to network experience.LTE optimization faces many challenges.Therefore,China Mobile Shandong Corporation made a complete and feasibility solution,which met the requirement of high-speed scene optimization.There were four dimensions in this solution: double layers network deployment,VoLTE optimization of high-speed rail,coordinating optimization in the boundary of high-speed network and normal LTE network,and the exploration and deployment of new functions.After the implementation of the solution,VoLTE coverage rate increases from 87.95% to 91.66%,MOS value upgrades from 3.6 to 4,the ratio of MOS value greater than 3.0 rised from 89.61% to 96.70%.